Research and Application of Testing Technology of Cloud Computing Database - Hongfei Qiu; Xianxu Li; Chunguang Huang (Dianxin kexue)
The infrastructure of database products was briefly introduced.Aiming at the performance of cloud computing database under the workload of business type,testing technology standard of cloud computing database was especially analyzed,and the evaluate and assessment methods of capacity of cloud computing database was expatiated.